Zooplankton composition and density in the Tucuruí hydroelectric plant reservoir (Pará, Brazil) (Research, Society and Development, 2020)
The study of zooplankton in reservoirs has been increasingly performed due to the role and characteristics of organisms. The Tucuruí reservoir presents few and widely spaced studies generating a gap in the knowledge of the composition and density of zooplankton in that region. Therefore, the objective was to describe the composition and density of the zooplankton in the Tucuruí reservoir in the months of february, july and december 2011. Samples were performed in 10 collection stations along the reservoir. The samples were collected with 64 µm plankton nets. With 156 taxa of zooplanktonic organisms identified, the rotifers had the highest species richness (88), followed by cladocerans (24) and copepods (13). Testaceous amoebae occurred sporadically. The richness varied significantly in relation to the months, and the Simpson index was significantly higher in February, while the density of organisms did not show significant variation. The density was dominated by the species of rotifer Keratella americana and nauplii throughout the study, contributing about 50% of the abundance. Thus, the zooplankton community showed typical composition and density for Amazonian ecosystems, with the rate domain like Rotifera and Copepoda being frequent during sampling.